PEMBEKALAN PERENCANAAN KEUANGAN BAGI ATLET ANGKAT BESI KLUB TEGAR BERIMAN - Eri Bukhari; Bintang Narpati; Adi Wibowo Noor Fikri; M. Fadhli Nursal; Tyna Yunita (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2021)
Financial planning is very important for individuals or families, especially in terms of regulating and managing existing finances. The purpose of this activity is to provide counseling to the weightlifting athletes of the 'Tegar Faith' club who are members of the PB PABSI. The reason for the importance of this activity is that the productive age for athletes is generally short, especially athletes who rely on physical activity in their activities, so that many athletes who retire at a relatively young age then experience financial difficulties. Talking about the retirement of an athlete, especially for the sport of Weightlifting, is almost certainly very short. Usually they are successful at the age of 17 to 25 years because at that age the athletes reach their golden age. It is conceivable if an athlete has passed his golden age, but cannot manage his finances properly. If this condition is not prepared from the start, it will have an impact on the economic security of the athlete's family if he is no longer an athlete. The method used is to make observations by systematically observing and recording the symptoms / phenomena being investigated, how phenomena that often occur among former athletes, then determining the theme of service, namely financial planning for athletes. The results of this financial planning briefing are expected by athletes The weightlifters, especially those who are members of the